THE INFLUENCE OF REWARDS AND EMPLOYEE EMPOWERMENT ON WORK PERFORMANCE AT THE SECRETARIAT OF THE REGIONAL HOUSE OF REPRESENTATIVES (DPRD) OF NORTH SULAWESI PROVINCE WITH CREATIVITY AS AN INTERVENING VARIABLE - Ibrahim, Driyana; Sendow, Greis M.; Pandowo, Merinda H. Ch. (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
This study aims to analyze the influence of rewards and employee empowerment on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of North Sulawesi Province, with creativity as an intervening variable. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees at the Secretariat of DPRD North Sulawesi Province. The analytical technique used is path analysis. The findings indicate that rewards do not significantly influence creativity or employee performance. Additionally, the effect of rewards on employee performance through creativity is also not significant. Meanwhile, empowerment has a significant impact on both creativity and employee performance. However, creativity as an intervening variable does not provide a significant effect in the relationship between rewards and empowerment on employee performance. This study provides new insights into the role of creativity as an intervening variable and suggests that organizations should focus more on employee empowerment strategies to enhance performance.